2020
DOI: 10.1109/access.2020.3025292
|View full text |Cite
|
Sign up to set email alerts
|

Research on SCESS-DFIG DC Bus Voltage Fluctuation Suppression Strategy for Frequency Inertia Regulation of Power Grid

Abstract: The doubly fed induction generator with super capacitor is helpful to enhance the system inertia. At the same time, its structural characteristics are more suitable for the power grid topology without communication lines. However, the change of its topology also brings some problems. In this paper, when SCESS-DFIG is participating in frequency regulation, DC bus voltage fluctuation caused by power imbalance of multiple converters is studied. The dynamic power response of super capacitor with DC-DC converter is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…i) In order to achieve the specified control objectives in the non-ideal grid condition, the fundamental, negative and harmonic components of the grid tension must be extracted. The extraction process would use numerous notch and low pass filters; therefore, phase delay and control error would be unavoidable [15]. ii) In order to implement the different control targets by employing voltage oriented control (VOC) or direct power control (DPC) strategy, the control reference calculation of rotor current in VOC or active/reactive power in DPC is always complicated and time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…i) In order to achieve the specified control objectives in the non-ideal grid condition, the fundamental, negative and harmonic components of the grid tension must be extracted. The extraction process would use numerous notch and low pass filters; therefore, phase delay and control error would be unavoidable [15]. ii) In order to implement the different control targets by employing voltage oriented control (VOC) or direct power control (DPC) strategy, the control reference calculation of rotor current in VOC or active/reactive power in DPC is always complicated and time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, existing research has suggested using wind turbine energy storage devices as power absorption elements to fulfill the system's frequency regulation needs [15]. The distributed energy storage architecture is provided by [16]. The DC-DC converter connects the energy storage device to the wind turbine DC bus.…”
Section: Introductionmentioning
confidence: 99%
“…However, the synthetic inertia capability of WTs strongly depends on wind speed, and it cannot be guaranteed under all wind conditions (Gloe et al, 2019). Though, there is the possibility of integrating wind generation units with EES, such as batteries (Ma et al, 2017;Watson et al, 2018;Dhundhara and Verma, 2020), supercapacitors (Sun et al, 2020) or FESS (Akbari and Izadian, 2021) for improving turbine's synthetic inertia performance, these are related to additional infrastructure cost. Still, relatively frequent shutdowns caused by low wind represent an unsurpassed drawback.…”
Section: Introductionmentioning
confidence: 99%